Efektivitas Penegakan Hukum Wakaf Produktif Dalam Perspektif Undang-Undang Nomor 41 Tahun 2004: Studi Empiris Pada Lembaga Nazhir - Slamet Slamet; Ahmad Kafiy; Niken Ayu Muslimatul Jannah; Moh Salman Al Faruq (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2026)
Productive waqf is an Islamic economic instrument with strategic potential to promote the welfare of the community if managed professionally and accountably. Law Number 41 of 2004 concerning Waqf provides a comprehensive legal basis for the management of productive waqf, particularly through the regulation of the roles and responsibilities of nazhir (the trustee). However, the effectiveness of productive waqf law enforcement in practice still faces various obstacles. This study aims to analyze the effectiveness of productive waqf law enforcement from the perspective of Law Number 41 of 2004 through an empirical study of nazhir institutions. This study uses an empirical juridical method with a qualitative approach supported by descriptive quantitative data. Data were obtained through literature review, field observations, and interviews and questionnaires with nazhir at several waqf institutions in East Java. The results indicate that the effectiveness of productive waqf law enforcement is moderate. Although an adequate legal framework is in place, its implementation is hampered by the low competence and legal literacy of nazhir, weak oversight by relevant institutions, and the suboptimal application of legal sanctions. This study concludes that the effectiveness of productive waqf law enforcement requires strengthening the capacity of nazhir, improving the integrated monitoring system, and ongoing socialization of waqf law so that productive waqf can function optimally as an instrument of empowerment and welfare of the people as mandated by Law Number 41 of 2004.